Exploration of the uptake of asymptomatic COVID-19 lateral flow testing in Birmingham, UK: survey and qualitative research. Issue 4 (20th April 2022) - Mathers, Jonathan; Poyner, Christopher; Thompson, Dean; Rudge, Gavin; Pritchett, Ruth V
Abstract : Aim: To examine public perspectives on lateral flow testing (LFT) for COVID-19. Design: Online survey with nested semi-structured interviews. Setting: Birmingham, UK. Participants: 220 Birmingham residents, 21 of whom took part in an interview. Results: Fifty-six per cent of respondents had taken an LFT. Reasons for not testing included adherence to other government COVID-19 guidance, having had a vaccination and not thinking LFTs were accurate. In 16% of households with children nobody, including children, was testing. In households where children were testing, their parents or other adults were often not. Those who were testing and eligible for workplace and school testing were more likely to be testing twice weekly. In other settings, respondents were more likely to be testing on a one-off or ad hoc basis. Approximately half of respondents said that they were likely to visit friends and family after a negative test result and 10% that they were unlikely to self-isolate following a positive test result. In interviews, participants who were testing described the peace of mind that testing afforded them prior to activities or interactions with family and friends, including those they considered to be vulnerable. Interviewees who were not testing described concerns about test accuracy and also cited a lack of face-to-face interaction with others precluding the need to test. Participants were often testing flexibly according to circumstances and perceived risk of COVID-19 transmission. Conclusions: While some choose not to test, others are doing so in order to provide peace of mind to engage in personal interactions they might otherwise have avoided. This peace of mind may be a necessary pre-requisite for some to more fully re-engage in pre-pandemic activities. Despite clear concerns about test accuracy among those not testing, those who are testing held generally positive attitudes towards the continued use of LFTs.